2020
DOI: 10.2147/rmhp.s280656
|View full text |Cite
|
Sign up to set email alerts
|

<p>Who Misses Appointments Made Online? Retrospective Analysis of the Outpatient Department of a General Hospital in Jinan, Shandong Province, China</p>

Abstract: Purpose: Missed appointments in outpatient registration pose challenges for hospital administrators, especially in the context of China's shortage of medical resources. Previous studies have identified factors that affect healthcare access via traditional appointment systems. Few studies, however, have specifically investigated Internet appointment systems. Therefore, this study explored the key factors related to missed appointments made on the Internet appointment system of a general hospital in Jinan, Shand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Illuminating variations in online mutual aid experiences has utility, as it points to potential demographic factors that could be the subject of further empirical enquiry. Extant research has highlighted demographic variables associated with engagement with various online services, relating to age (DeAndrea & Anthony, 2013; Su et al, 2020), minority subgroups (DeAndrea & Anthony, 2013) and income (Lucas et al, 2020). Future quantitative research could examine the relationship between variables associated with digital poverty 6 and online service outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Illuminating variations in online mutual aid experiences has utility, as it points to potential demographic factors that could be the subject of further empirical enquiry. Extant research has highlighted demographic variables associated with engagement with various online services, relating to age (DeAndrea & Anthony, 2013; Su et al, 2020), minority subgroups (DeAndrea & Anthony, 2013) and income (Lucas et al, 2020). Future quantitative research could examine the relationship between variables associated with digital poverty 6 and online service outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Habibi et al [14] investigated the effect of online appointment scheduling system by a before and after study, which shows that DSS could reduce patient waiting time and no-show rates, increased physician punctuality, and facilitated continuous quality improvement of outpatient services. Su et al [15] pointed out that DSS has shown unprecedented predictive value in allocating medical resources by considering the factors of no-show events. Besides, the impact of DSS in improving scheduling efficiency, staff workforce, and institutional benefits has also been widely reported [16,17].…”
Section: Introductionmentioning
confidence: 99%